Maintenance CBT in Preventing Relapse in Patients on SSRI Continuation - D. Peselow, Eric (Current Psychopharmacology, 2013)
The utility of cognitive-behavioral therapy in the treatment of acute depression has been well established. It is frequently employed with antidepressants acutely to yield greatest efficacy. While it is frequently stated that the techniques of CBT learned during acute treatment are enduring, there is little data suggesting that this is true. We studied 327 patients over a 13 year period in a community clinic who responded to one of four Selective Serotonin Reuptake Inhibitors (SSRI's) with a 50% reduction in Montgomery Asberg Score after 12 weeks treatment. SSRI's used were fluoxetine, citalopram, paroxetine and sertraline. The patients were all followed on the medication to which they responded until they either relapsed, dropped out, or terminated well (were well as of September 1, 2005 the endpoint of the study). Overall, 110 patients acutely received CBT in addition to the SSRI and 217 did not. Following acute response 35 of the 110 patients who received CBT acutely elected to continue CBT in addition to the medication and 75 did not. Overall, the group that continued CBT remained well for 49.60 months as opposed to 34.77 months for those who did not continue CBT vs 30.78 months for those who only received drug alone. Pairwise comparisons using the Scheffe show that longterm CBT results in significantly more time of stability than either acute CBT (p=.039) or drug alone (p=.001). Acute CBT and Drug Alone did not differ significantly from each other (p=0.58).. Interestingly the 75 patients who received CBT acutely but not for maintenance did not remain well longer than the 217 patients who did not receive CBT acutely (34.77 vs 30.78 p=0.58). In conclusion, CBT in addition to medication during acute treatment did not endure for the long-term. However maintenance CBT in addition to SSRI's was effective in preventing relapse.
Keywords: Cognitive behavioral therapy (CBT)